2013
DOI: 10.5539/ass.v9n5p235
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Vocabulary Acquisition through Computer Game: A Case Study

Abstract: Learning vocabulary is not easy and it may be very frustrating to some learners. Many approaches have been taken to attract learners to learn new vocabulary. The aim of this case study is to explore how a computer game can be adapted as a learning tool to sustain adult vocabulary learning independently. This study used the existing SIM 3 game as a selected platform to investigate the vocabulary learning among ESL adult learners in an independent learning environment. Three adult ESL learners from different bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
2
17
0
2
Order By: Relevance
“…Lai (2010) regarded learning motivation as the inherent belief to guide individual learning goals, induce learning behavior for continuous efforts, reinforce cognitive process, and enhance and improve learning outcome. According to value-expectancy model, proposed by Bakar & Nosratirad (2013), ability belief, success expectancy, and work value are important variables of learning motivation in student' self-learning regulation process. Ability belief refers to students perceiving personal ability when engaging in learning.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…Lai (2010) regarded learning motivation as the inherent belief to guide individual learning goals, induce learning behavior for continuous efforts, reinforce cognitive process, and enhance and improve learning outcome. According to value-expectancy model, proposed by Bakar & Nosratirad (2013), ability belief, success expectancy, and work value are important variables of learning motivation in student' self-learning regulation process. Ability belief refers to students perceiving personal ability when engaging in learning.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…A number of qualitative studies [23] [24] revealed strategies that second language learners found useful for vocabulary facilitation through gaming situations. Students named, guessing from the context [23]- [25], using of dictionaries [23] [26]- [28], peers' advice [23] [25] [27], language repetitions [25] [27] [29], and interactions with native speakers [30] as the most helpful. Moreover, students in these studies reported the enhanced motivation toward language learning caused by engaging gaming environment.…”
Section: Vocabulary Learning Strategiesmentioning
confidence: 99%
“…Moreover, 91% of second language learners find them helpful [9]. Bakar and Nosratirad [27] revealed positive effects of frequent and repeated usage of words in different gaming situations for vocabulary acquisition. Three adult low-level English proficiency learners independently acquired over 120 words through The Sims after two months of playing for approximately 4.5 hours per week.…”
Section: Cognitive Strategies: Verbal and Written Repetitionsmentioning
confidence: 99%
“…Abu Bakar and Nosratirad (2013), conducting a case study and using a computer game, intended to explore how much adult learners sustain vocabulary independently and to explore how a computer game could encourage adult learners to learn English vocabulary independently. To this end, a qualitative research method was used in this study.…”
Section: International Studiesmentioning
confidence: 99%